IMPROVING GOURAMI LARVAE GROWTH WITH TUBIFEX WORMS AND VITAMIN D COMBINATION - Karyati, Dewi; Nainggolan, Armen (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2024)
Research activities will be carried out for two months and a half in May until July 2017. The research was conducted in analysis at Cianjur Fishing Seed Center (PPISHP). The purpose of this research is to know the effect of vitamin D addition on silk worm to growth of carp larvae and to know dose Vitamin D in the appropriate silk worm to increase growth of carp larvae. The method used for this research is the method of observation while the design used is Completely Randomized Design (CRD). And a test consisting of 5 treatments with each of 3 replications. Treatment was the addition of vitamin D with different doses of 0 mg / l, 25 mg / l, 50 mg / l, 75 mg / l, and 100 mg / l. The best result is the best dose to increase the growth of carp larvae weight is dose 25 mg / l weight of 3 gram, the length increase 3,1 cm, and the survival rate 88%. Water quality parameters during the study temperature of 27-28 º C, pH 6,5-7.5, dissolved oxygen 3-5 mg / l, and NH3 ammonia 0,1-0.2 ppm.